Lead switching to resolve undersensing of ventricular tachycardia by a cardiac resynchronization therapy defibrillator. Issue 3 (27th October 2022) - Kataoka, Shohei; Yagishita, Daigo; Yazaki, Kyoichiro; Hasegawa, Shun; Kanai, Miwa; Ejima, Koichiro; Shoda, Morio
Abstract: A 63‐year‐old man was admitted to the hospital due to ventricular tachycardia (VT) undersensing, caused by decreased R‐wave amplitude in a cardiac resynchronization therapy defibrillator. The R‐wave amplitude of VT sensed by the left ventricular (LV) lead was markedly higher than that by the right ventricular (RV) lead; therefore, we reconnected the IS‐1 RV lead to the LV IS‐1 port and the IS‐1 LV lead to the RV IS‐1 port to resolve this issue. After discharge, it was confirmed that VT was successfully terminated by the second sequence of intrinsic ATP (iATP, Medtronic, Minneapolis, MN, USA) from the LV lead.